2009
DOI: 10.17925/use.2009.05.1.34
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Insulin in the Regulation of PEPCK and Gluconeogenesis In Vivo

Abstract: The regulation of gluconeogenesis by insulin is complex and can involve insulin-mediated events in the liver, as well as in several non-hepatic tissues. Given the complexity of this regulation, it is no surprise that there is considerable debate regarding insulin’s ability to regulate the rate of gluconeogenic formation of glucose-6-phosphate (GNG flux to G6P)in vivo. Conventional ‘textbook’ teaching (based onin vitrostudies of rat liver) depicts that insulin can inhibit this pathway by suppressing the transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…This finding fits with data from studies that showed that the gluconeogenic pathway was not suppressed by meal-associated hyperinsulinemia (23–25), despite insulin’s ability to suppress PEPCK protein expression (15). Thus, the rapid effects of insulin on hepatic glucose metabolism in the current study were the consequence of glycogenolytic inhibition and the redirection of gluconeogenic carbon into glycogen, not a reduction of gluconeogenic flux to glucose-6-phosphate (15,20,26,27). Interestingly, although brain-insulin signaling created differences in GK and GSK3β protein, those changes did not translate into an increase in hepatic glucose uptake, as was seen in the presence of selective brain hyperinsulinemia in our earlier study (12) or a decrease in EGP, as was shown in rodent studies (111).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This finding fits with data from studies that showed that the gluconeogenic pathway was not suppressed by meal-associated hyperinsulinemia (23–25), despite insulin’s ability to suppress PEPCK protein expression (15). Thus, the rapid effects of insulin on hepatic glucose metabolism in the current study were the consequence of glycogenolytic inhibition and the redirection of gluconeogenic carbon into glycogen, not a reduction of gluconeogenic flux to glucose-6-phosphate (15,20,26,27). Interestingly, although brain-insulin signaling created differences in GK and GSK3β protein, those changes did not translate into an increase in hepatic glucose uptake, as was seen in the presence of selective brain hyperinsulinemia in our earlier study (12) or a decrease in EGP, as was shown in rodent studies (111).…”
Section: Discussionmentioning
confidence: 62%
“…That being said, we saw no impact of brain-insulin action on EGP even in the fourth hour of hyperinsulinemia, whereas in the rat, there was an ∼30% decrease at 2 h. Finally, glucose metabolism is different in rodents and large animals in several regards (e.g., the rodent has much higher basal rates of EGP, more complete glycogen depletion during fasting leading to an enhanced gluconeogenic contribution to EGP, differing hepatic neuroanatomy, etc.) (12,27,28), and it is possible that rodents have increased sensitivity of the gluconeogenic pathway to brain insulin–mediated inhibition compared with species with greater dependence on glycogenolysis.…”
Section: Discussionmentioning
confidence: 99%
“…This result was corroborated by upregulation of genes in the glycolysis/gluconeogenesis pathway ( Figure 4B and Supplemental Figure 4). Insulin normally inhibits gluconeogenesis by inhibiting transcription of phosphoenolpyruvate carboxykinase 1 (PCK1), which is important in catalyzing the first committed step in gluconeogenesis (22). However, PCK1 was upregulated by the lipotoxic milieu ( Figure 4B), suggesting that the cells have become unresponsive to insulin.…”
Section: Resultsmentioning
confidence: 99%
“…However, PCK1 was upregulated by the lipotoxic milieu ( Figure 4B), suggesting that the cells have become unresponsive to insulin. To determine if altered glucose regulation was due to reduced insulin sensitivity, we measured glucose output following an insulin challenge, as insulin should inhibit gluconeogenesis and promote glycolysis (22). Hepatocytes exposed to a lipotoxic milieu were unable to reduce their glucose secretion with an insulin challenge, while the hepatocytes exposed to a healthy milieu exhibited a 4-fold reduction in glucose secretion ( Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is unlikely that acute changes in brain insulin signaling, which appear to involve the genetic regulation of gluconeogenesis, would produce an effect on HGP during the time-course of a meal. Instead, it would appear that the non-genomic (post-translational) mechanisms are responsible for the rapid insulin-mediated suppression of HGP (Lin and Accili, 2011; Ramnanan et al, 2010a). …”
Section: Further Considerationsmentioning
confidence: 99%